LTE mobile equipment mutual interference - Stancheva, Anushka; Kadrev, Vasil (Yearbook Telecommunications, 2017)
Nowadays, LTE networks are becoming more and more popular. The subscribers’ demands for even faster data traffic are constantly increasing and force mobile operators to increase the capacity and cell coverage of the network to meet this challenge. Another challenge in this dynamically changing environment is the efficient use of spectrum and the satisfactory quality of services provided to users. However, increasing the capacity and coverage of networks based on the use of the same bandwidth in neighboring cells leads to serious inter cell interference, especially at the cell boundaries. The purpose of this article is to outline the types of interference that may arise between mobile phones/user equipment, including interference in direct communication between user devices (D2D communications), as well as examining and analyzing typical problem situations. Based on a subjective and objective analysis of freely available literary sources, the report outlines the methodologies for real-time management of interference from UEs in LTE networks that are often used by operators and suggested solutions to suppress/mitigate this type of interference.